Perancangan Alat Bantu Pengambilan Kain pada Proses Pengukuran dan Pemotongan di Konveksi Printrend dengan Metode Rasional - Madani, Aqshal; Ramadhani, Fahmi; Setyowati, Linda; Mutmainah, Mutmainah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Cutting and Measur ing Process at CV. Printrend Convection has several work activities. However, the work activity when taking the fabric below, which is done repeatedly by bending, is not ergonomic. Based on the results of the RULA method, this attitude is high risk, and the final score obtained is 7, so it is high risk, and changes are made now. Therefore, a design was made to reduce the final RULA score using the rational method, the height of the design is based on the anthropometry of the worker's Standing Height with the 10th percentile. Then, the use of the design is simulated with Catia to determine the final RULA score. Based on the simulation results, pulling fabric from the fabric hanging tool and taking fabric from below with a new work attitude gets a final RULA 3 low-risk score. The activity of taking fabric from the highest fabric rack based on the simulation with Catia receives a final score of RULA 2 with a work attitude whose risk can be ignored. From the simulation results, the design succeeded in reducing the final RULA score and it’s risk level